Evolution and Comparative Genomics of Odorant- and Pheromone-Associated Genes in Rodents - Emes, Richard D.; Beatson, Scott A.; Ponting, Chris P.; Goodstadt, Leo (Genome Research, 2004)
Chemical cues influence a range of behavioral responses in rodents. The involvement of protein odorants and odorant receptors in mediating reproductive behavior, foraging, and predator avoidance suggests that their genes may have been subject to adaptive evolution. We have estimated the consequences of selection on rodent pheromones, their receptors, and olfactory receptors. These families were chosen on the basis of multiple gene duplications since the common ancestor of rat and mouse. For each family, codons were identified that are likely to have been subject to adaptive evolution. The majority of such sites are situated on the solvent-accessible surfaces of putative pheromones and the lumenal portions of their likely receptors. We predict that these contribute to physicochemical and functional diversity within pheromone-receptor interaction sites.
10.1101/gr.1940604